Applications of actuarial techniques to credit default swap pricing - Lim, Zheng Xian (2012)
The objective of this project is to investigate the credit spread of credit default swaps by using actuarial techniques. The group quantifies the CDS spread by firstly calculating the default rates of selected bonds using actuarial means of calculating mortality rates of bonds. The default rates were then smoothed before inputting into a pricing model to calculate the CDS spread of a Credit Default Swap Index (Markit CDX). This spread is then compared to the current Markit CDX spread.